ANALISIS KESIAPAN RSUD KAREL SADSUITUBUN LANGGUR DALAM IMPLEMENTASI REKAM MEDIS ELEKTRONIK: Analysis of the Readiness of Karel Sadsuitubun Langgur Hospital in the Implementation of Electronic Medical Records - Ikawati, Fita Rusdian; Rusfadir, Agustina; Leby, Maria Faustina (ASSYIFA : Jurnal Ilmu Kesehatan, 2024)
A hospital is a group that medical professionals do in a well-structured manner. Electronic medical records are a transition from manual to computerized patient medical records. The function of electronic medical records in general is to improve the quality of services provided to patients. The method used in this study is a descriptive qualitative method and data collected through observation and interviews, the informants in this study are 3 people, namely the head of the medical record coordinator, registration officer and IT officer. Factors that hinder the readiness to implement electronic medical records include 3 aspects, namely: Human resources (HR), infrastructure and information technology (IT). The results obtained at the Karel Sadsuitubun Langgur Hospital are the lack of understanding and knowledge of officers related to electronic medical records, inadequate computers in the polyclinic room due to cost constraints, and the lack of integration with Satu Sehat. The readiness of the implementation of electronic medical records at Karel Sadsuitubun Langgur Hospital is still hampered by these 3 aspects so that there is a need for socialization and training to officers, the holding of computers in each polyclinic room so that services can run optimally and immediately cooperate with Satu Sehat.